Implementasi Wireless Sensor Network Pada Simulasi Peringatan Gempa Bumi Menggunakan Sensor SW-420 - Mukhamad Ishomyl (Politeknik Negeri Malang, 2020)
The wireless sensor network is a network consisting of sensor devices that detect nearby symptoms and then send information about the obtained results. Earthquakes are natural phenomena that can come at any time. So we need a tool that works automatically to give a warning as soon as possible when a WSN-based earthquake occurs to anticipate community rescue and reduce the number of casualties. This earthquake simulation alert will provide two notifications. Visual notifications displayed on the LCD and from the web. The sound notification issued by the buzzer will be different depending on the vibration received by the SW-420 sensor. Parameter earthquake used is MMI (modified mercalli intensity) using a visual assessment, international earthquake parameters. SIG (earthquake intensity scale) which already has a PGA (Peak Ground Acceleration) unit and includes MMI in it which is made by BMKG. After an excessive vibration is detected and it exceeds a predetermined limit, the MCU node will send an analog signal to the buzzer to provide a notification that has been set. For each appear notification, it aims to direct the public as soon as possible to assembly point that has been set in each building. Each detected vibration will be stored in WEB database. The vibration results detected by the sensor are a value of 0 (low) and 1 (high). These results will be sampled and produce an output in the form of Earthquake Intensity Scale.